Perlindungan Konsumen dalam Perspektif Norma Bisnis Islam - Zahrotul Maásah (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Consumer protection is not a new thing in the life of a very diverse Indonesian society, but violations of consumer protection are not uncommon, consumers are always in a very weak position, and ironically consumers, especially in Indonesia, are not all able to thoroughly and critically evaluate a product. goods and services, so that they can be easily deceived by producers. This is very important to discuss in relation to Islamic business norms and comparisons between consumer protection in Indonesia, bearing in mind that negligence or intentional production or in providing services will have a detrimental impact on consumers and society in general. In its implementation, this research is classified as normative research using the statue approach method and the study of the results of this research is carried out using descriptive-analytic discussion. As for the sources of legal materials used by various laws and sources of Islamic law (al-Qur'an and Hadith) and scientific works related to the issue of consumer protection. Critical identification and inventory procedures are then followed through a systematic logical clarification process in accordance with the theme formulated in the purpose of this study.